2020
DOI: 10.1007/s00784-020-03501-3
|View full text |Cite
|
Sign up to set email alerts
|

Leptin reduces in vitro cementoblast mineralization and survival as well as induces PGE2 release by ERK1/2 commitment

Abstract: Objectives Juvenile obesity is a complex clinical condition that is present more and more frequently in the daily orthodontic practice. Over-weighted patients have an impaired bone metabolism, due in part to their increased levels of circulating adipokines. Particularly, leptin has been reported to play a key role in bone physiology. Leptin is ubiquitously present in the body, including blood, saliva, and crevicular fluid. If, and to what extent, it could influence the reaction of cementoblasts during orthodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In a previous study, we have shown that blockade of ERK1/2 impairs leptin-induced Caspase 3 and Caspase 9 expression on OCCM-30 cells ( Ruiz-Heiland et al, 2020 ). ( Kadowaki et al, 2006 ) observed that Adiponectin induces osteogenesis via P38 through AdipoR1, but not AdipoR2 on C3H10/T2 cells up-regulating the expression of Runx-2 ( Kadowaki et al, 2006 ).…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we have shown that blockade of ERK1/2 impairs leptin-induced Caspase 3 and Caspase 9 expression on OCCM-30 cells ( Ruiz-Heiland et al, 2020 ). ( Kadowaki et al, 2006 ) observed that Adiponectin induces osteogenesis via P38 through AdipoR1, but not AdipoR2 on C3H10/T2 cells up-regulating the expression of Runx-2 ( Kadowaki et al, 2006 ).…”
Section: Discussionmentioning
confidence: 95%
“…When the process reaches a certain balance, the normal morphology and function of alveolar bone can be maintained. Additionally, one of the most important factors in orthodontic tooth movement is bone resorption caused by osteoclasts [ 12 ]. Recently, many studies have focused on how osteoclast differentiation influences orthodontic tooth movement and the mechanism behind this process [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, M1 participates in the expression of cytokines, such as PGE2, IL-1β, TNF-α, IL-6 and IL-12, which are considered to be crucial players in the progression of PD and bone absorption. Among them, PGE2 is the most powerful stimulating factor of periodontal bone resorption, mediating various destruction processes of alveolar bone and cementum, such as reducing the mineralization and survival ability of osteoblasts, mediating the formation of osteoclasts, and stimulating the transformation of cementoblasts into cementum cells ( 54 , 55 ). LPS is an activator of IL-1β expression in M1, and IL-1β and TNF-α can also activate M1 to produce IL-1β, promoting the activation and differentiation of osteoclasts and ultimately causing bone resorption ( 56 ); TNF-α can also induce RANKL production by T cells and B cells ( 32 ).…”
Section: Polarization Of Macrophages In Periodontitis and Its Role In Periodontitis Pathophysiologymentioning
confidence: 99%